(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
In thc Southern Alps the boundary between the marine Upper Permian Bellerophon Formation and the Scythian Werfen Formation was believed to coincide with the Permo—Triassic boundary. Almost everywhere in the area from Recoaro (Vicenza) to the Badia Valley (Northern Dolomites) (Fig, l) the lower part of the Wcrfen Fm. is represented by the Mazzin Member dated as Early Griesbachian (Broglio Loriga et al., 1980, 1982; Mostler et al., 1982). The Mazzin Member begins with the Tesero oolitic Horizon (Bosellini, 1964, 1968), which consists of oolitic grainstones with dolomitized ooids and it ig considered to be trasgressive on the Bellerophon Fm. (Bosellini, 1964; Assereto et al., 1973; Cassinis et al., 1979; Farabegoli & Vicl, 1982; etc.). The Upper Bellerophon Fm. has been correlated with the Caucasian Phisonites—comelicania zone (Assereto et al., 1973), today referred to Lower Dorashamian (Rostovtsev & Azaryan, 1973).